OPPORTUNITIES AND CHALLENGES FOR MSMEs IN INDONESIA IN THE FACE OF RAMADAN - Rijal, Syamsu; Ausat, Abu Muna Almaududi; Kurniawati, Rina; Suherlan, Suherlan (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The month of Ramadan has an impact on the Indonesian economic sector, especially on MSMEs. For example, the demand for food and beverages increases during iftar and suhoor, so culinary businesses such as food stalls and street food vendors can experience an increase in turnover during the month of Ramadan. However, MSMEs also face various challenges such as a decrease in people's purchasing power. This study aims to analyse the opportunities and challenges faced by MSMEs in Indonesia during Ramadan, as well as the efforts that can be made to optimise opportunities and overcome these challenges. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study arrive at the conclusion that MSMEs in Indonesia have great opportunities during the month of Ramadan, especially in the food and beverage sector. These opportunities can be utilised by improving product quality, maintaining inventory, using social media for marketing, offering discounts and special offers, establishing partnerships, maintaining service quality, and utilising digital potential.